Median *ganza- as loanword - Lipiński, Edward (Anabasis. Studia Classica et Orientalia, 2014)
The Iranian word *ganza-, ‘store, treasure’, and some of its derivatives have been adopted at the time of the Persian Achaemenid Empire by several Semitic languages, especially by Aramaic and then by Ethio-Semitic and the Greek idiom spoken in the Middle East. The article offers an overview of these loanwords and their variants, sometimes implying linguistic changes caused by the assimilation nz > zz, a partial assimilation of the short a to the plural ending -ē of the Aramaic and Hebrew construct state or the palatalization of z in Amharic. The word Ginza designates the main Mandaean holy book and ‘genizah’ became the name of the storage place of sacred books and other writings in Jewish tradition. The word ginzē has sometimes been confused with gizzē, dissimilated into ginzē ‘wool coats’, especially in the Book of Ezekiel 27:23, referring to Phoenician trade in wool fabrics from 7 th -century Assyria and Shubria.